Improving writing ability through cooperative learning strategy - Sabarun, Sabarun (Journal on English as a Foreign Language (JEFL), 2011)
The objective of the study was to improve the studentsâ writing ability in writing English class using Cooperative Integrated Reading and Composition (CIRC) model of Cooperative learning strategy. The study employed Classroom Action Research (CAR) design. The subjects of the study were the fifth semester students of the English Department of Malang Muhammadiyah University. The numbers of the subjects were 5 students. The study was conducted in two cycles with 4 steps of classroom action research procedure: planning, implementing, observing and reflection. Each cycle had two meetings. The result of the study showed that Cooperative learning strategy with Cooperative Integrated Reading and Composition (CIRC) model was effective to improve the studentsâ writing ability that could be seen from the improvement of the studentsâ writing achievement.